1999
DOI: 10.1128/jvi.73.6.4575-4581.1999
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Human T-Lymphotropic Virus Type 1 (HTLV-1)-Infected Dendritic Cells in the Development of HTLV-1-Associated Myelopathy/Tropical Spastic Paraparesis

Abstract: The development of human T-lymphotropic virus type 1 (HTLV-1)-associated myelopathy/tropical spastic paraparesis (HAM/TSP) is closely associated with the activation of T cells which are HTLV-1 specific but may cross-react with neural antigens (Ags). Immature dendritic cells (DCs), differentiated from normal donor monocytes by using recombinant granulocyte-macrophage colony-stimulating factor and recombinant interleukin-4, were pulsed with HTLV-1 in vitro. The pulsed DCs contained HTLV-1 proviral DNA and expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 27 publications
3
49
0
1
Order By: Relevance
“…In the present study, we show that, after coculture of HTLV-1-infected cell lines with human DCs, viral particles can be detected within DC vacuoles as early as 3 h after contact and infection of DCs can be observed by immunofluorescence. DC infection is compatible with data obtained in vivo, which demonstrate infection of DCs in HTLV-1-infected asymptomatic carriers (12) and in TSP/HAM patients (20,24,25). HTLV-1 infection does not generally occur through cell-free virions, but rather by direct cell-cell transfer between lymphocytes (13), with involvement of cytoskeletal polarization (5).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the present study, we show that, after coculture of HTLV-1-infected cell lines with human DCs, viral particles can be detected within DC vacuoles as early as 3 h after contact and infection of DCs can be observed by immunofluorescence. DC infection is compatible with data obtained in vivo, which demonstrate infection of DCs in HTLV-1-infected asymptomatic carriers (12) and in TSP/HAM patients (20,24,25). HTLV-1 infection does not generally occur through cell-free virions, but rather by direct cell-cell transfer between lymphocytes (13), with involvement of cytoskeletal polarization (5).…”
Section: Discussionsupporting
confidence: 85%
“…In the few papers devoted to the HTLV-1 infection of DCs, contradictory results have been reported. It was shown previously that DCs are susceptible to HTLV-1 infection in vitro (1,25,26), but another report indicated that DCs are not susceptible to HTLV-1 infection (48), as no evidence of virus uptake was observed after coculture with HTLV-1-infected cell lines. In the present study, we show that, after coculture of HTLV-1-infected cell lines with human DCs, viral particles can be detected within DC vacuoles as early as 3 h after contact and infection of DCs can be observed by immunofluorescence.…”
Section: Discussionmentioning
confidence: 92%
“…This scenario is also consistent with the concept of Tax cross-presentation by DCs. However, a small fraction of blood DCs (0.4 -5%) from HAM/TSP patients was found to be infected with HTLV-1 [48] and was shown to be susceptible to infection in vitro [45,49,50]. Therefore, we found it important to investigate direct presentation of Tax peptides by infected DCs along with the crosspresentation pathway.…”
Section: Figure 6 Confirmation Of Htlv-1 Infection In Cd4 ۉ /Cd25 ۉ mentioning
confidence: 99%
“…We have shown previously that DCs exhibit maximum binding affinity to cell-free HTLV-1 as compared with other cell types tested [47], indicating that these cells could be the first type interacting with HTLV-1, particularly during mucosal exposure. DCs obtained from patients with HAM/TSP were found to be infected with HTLV-1 [45,48] and can be infected easily in vitro by cell-free [45,49] and cell-associated [50,51] virus. Therefore, it is likely that infected DCs could process and present Tax antigen in the context of MHC class I, leading to the expansion of Tax-specific CD8 Ï© T cells.…”
Section: Htlv-1-infected Dcs Could Lead To the Proliferation Of Tax 1mentioning
confidence: 99%
“…The effect of Bay11-7082 and/or everolimus on allostimulatory capacity of DCs Activated DCs derived from healthy volunteers were potent stimulators of T-cell proliferation. 23 We next examined the function of DCs by using allogeneic mixed lymphocyte reactions. Mature DCs isolated from healthy volunteers potently stimulated the proliferation of lymphocytes ( Fig.…”
Section: The Effect Of Il-10 On DC Maturationmentioning
confidence: 99%